(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the effect of transformational leadership, employee engagement, and workload on employee performance with job satisfaction as an intervening variable at the Regional Secretariat of Dharmasraya Regency. The method used is quantitative with path analysis techniques, distributing 67 questionnaires. The research results show a positive but not significant effect of transformational leadership on job satisfaction at the Regional Secretariat of Dharmasraya Regency. There is a positive and significant effect of employee engagement on job satisfaction. There is a negative and significant effect of workload on job satisfaction. There is a positive and significant effect of transformational leadership on employee performance. There is a positive and significant effect of employee engagement on employee performance. There is a negative and significant effect of workload on employee performance. There is a positive and significant effect of job satisfaction on employee performance. Job satisfaction can mediate the effect of transformational leadership on employee performance. Job satisfaction can mediate the effect of employee engagement on employee performance. Job satisfaction can mediate the effect of workload on employee performance.